Radiobiology Experiments With Ultra-high Dose Rate Laser-Driven Protons: Methodology and State-of-the-Art - Chaudhary, Pankaj; Milluzzo, Giuliana; Ahmed, Hamad; Odlozilik, Boris; McMurray, Aaron; Prise, Kevin M.; Borghesi, Marco (Frontiers in Physics, 2021)
The use of particle accelerators in radiotherapy has significantly changed the therapeutic outcomes for many types of solid tumours. In particular, protons are well known for sparing normal tissues and increasing the overall therapeutic index. Recent studies show that normal tissue sparing can be further enhanced through proton delivery at 100 Gy/s and above, in the so-called FLASH regime. This has generated very significant interest in assessing the biological effects of proton pulses delivered at very high dose rates. Laser-accelerated proton beams have unique temporal emission properties, which can be exploited to deliver Gy level doses in single or multiple pulses at dose rates exceeding by many orders of magnitude those currently used in FLASH approaches. An extensive investigation of the radiobiology of laser-driven protons is therefore not only necessary for future clinical application, but also offers the opportunity of accessing yet untested regimes of radiobiology. This paper provides an updated review of the recent progress achieved in ultra-high dose rate radiobiology experiments employing laser-driven protons, including a brief discussion of the relevant methodology and dosimetry approaches.